Weaving the health and pharmaceutical care agenda through the themes of the commonwealth heads of government meeting (CHOGM), London 2018 - Victoria Rutter; Amy Hai Yan Chan; Chloe Tuck; Lina Bader; Zaheer-; Ian Bates (Taylor & Francis Group, 2018)
The biennial Commonwealth Heads of Government Meeting (CHOGM) this year is based around four key themes: prosperity, fairness, sustainability and security. This is an opportune time to consider the role of pharmacists in healthcare delivery, and particularly their contribution to achieving the United Nations Sustainable Development Goals (SDGs). As a member of the Commonwealth Health Professions Alliance (CHPA), the Commonwealth Pharmacists Association (CPA) has been working to ensure that pharmacy-related aspects of health are represented in the advocacy papers submitted by Civil Society. Echoing the CHPA's priorities around SDG 3 (health) and the attainment of sustainable universal health coverage (UHC), the CPA has been raising the profile of key priorities for our members, including: addressing the shortage of healthcare workers (with an emphasis on pharmacists); need for access to quality medicines and medicines information; tackling anti-microbial resistance and substandard/falsified medicines; and championing the role of digitalisation and partnerships. This editorial discusses how the work of the CPA links with the themes of CHOGM, the CPA's input into this meeting and the direction of travel 'Towards a Common Future' for health and pharmacy in the Commonwealth.